TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENIPUAN BERKEDOK ONLINE SHOP DI JEJARING SOSIAL FACEBOOK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFPRMASI DAN TRANSAKSI ELEKTRONIK - Nanda Agus, Vidya Tria; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
As time, in the field of technology development ensued. Technological development is seen with increasing public knowledge and curiosity are very big on this field, as well as the proliferation of existing facilities to make people can easily learn the technology. The media are used not only computers but laptops, tablets, mobile phones and assorted gadgets easy to carry anywhere and can access the internet is quickly becoming one of the forms of technological development.Crime in cyberspace commonly known as cybercrime. From the above information, the author makes some problem formulation in which the formulation of the problem in the form of how the rules of criminal fraud online shop in the guise of social networking facebook pursuant to Act No. 11 of 2008 on information and electronic transaction, what obstacles that arise in law enforcement efforts and the efforts that are that can be done to combat the crime of online fraud in the facebook social networking. Although the crime of fraud under the guise online shop can not be destroyed in total, the effort that can be taken to reduce such crime comes from the government and society itself. Due to the constraints of weakness in law enforcement criminal fraud through facebook that is in the process of investigation is difficult to meet the evidence, in addition to the need for technology to assist the police in the investigation process, in order to uncover criminal fraud through facebook as well as criminal offenses of this offense is a complaint. So the community is expected to work together in helping law enforcement officers that this problem can be reduced. So that the law can be enforced and efforts are made can achieve maximum results.